Lipin‐1 determines lung cancer cell survival and chemotherapy sensitivity by regulation of endoplasmic reticulum homeostasis and autophagy - Xueyu Fan; Yuanyuan Weng; Yongfeng Bai; Zongpan Wang; Siwei Wang; Jin Zhu; Feng Zhang (Cancer Medicine, 2018)
Abstract Cancer cells undergo comprehensive metabolic reprogramming to meet the increased requirements of energy and building blocks for proliferation. Lipin‐1, a phosphatidic acid phosphatase converting phosphatidic acid (PA) to diacylglycerol (DAG), is upregulated in lung adenocarcinoma (LUAD) cell lines and tumor tissues. In this study, we reveal high lipin‐1 expression is correlated with poor prognosis of patients with LUAD. Knockdown of lipin‐1 decreases cell viability and proliferation in LUAD cells, whereas it has less effect on nontumorigenic lung cells. Autophagy and ER stress play important roles in tumor initiation and progression. Lipin‐1 knockdown induces the initiation of autophagy while disrupts formation of autolysosome. Lipin‐1 silencing induces the activation of ER stress through the IRE1α pathway. Furthermore, we demonstrate disrupted ER homeostasis contributes to the cell phenotype, and the elevated autophagy initiation is due to the ER stress in part. For the first time, we show lack of lipin‐1 enhances the sensitivity of LUAD cells to cisplatin treatment. Our results suggest that lipin‐1 is a potential target, alone or combined with other treatment, for lung cancer therapy.